2015
DOI: 10.1007/s11604-015-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the ABC classification and radiological findings for assessing gastric cancer risk

Abstract: A good correlation exists between ABC classifications and radiological findings for gastric cancer risk, but some discrepant cases exist. We recommend both methods as screening for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Recently, Itoh et al also reported the aberration of high-risk subjects in group A by using radiologic findings [18]. In the present study, in the multicenter study we conducted in Japan, we clarified that (1) some gastric cancer patients were found in group A and (2) that only approximately 7% of all gastric cancer patients in group A were regarded as H. pylori uninfected.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, Itoh et al also reported the aberration of high-risk subjects in group A by using radiologic findings [18]. In the present study, in the multicenter study we conducted in Japan, we clarified that (1) some gastric cancer patients were found in group A and (2) that only approximately 7% of all gastric cancer patients in group A were regarded as H. pylori uninfected.…”
Section: Discussionsupporting
confidence: 53%
“…A previous report suggested that the subjects whose anti-H. pylori antibody titers were between 3 and 9.9 should be treated as having a high risk [18]. In addition, these subjects should receive gastrointestinal endoscopic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the original cut-off level of PG to diagnose the presence of gastritis [12,13,14]. Accordingly, we tried to add the new criteria for diagnosing and then classifying high-risk patients into group A to obtain better accuracy as follows: (1) negative-high Hp-Ab titer (3-9.9 U/mL); (2) PG II ≥15 ng/mL; (3) PG I/PGII ≤4.0; (4) PG I ≥100 ng/mL; and (5) any of the above.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we tried to add the new criteria for diagnosing and then classifying low-risk patients into group A to obtain better accuracy as follows: (1) exclude patients with negative-high Hp-Ab titer (3-9.9 U/mL) from group A [12]; (2) exclude patients with PG II ≥15 ng/mL from group A [13]; (3) change the criteria of ABC classification by PG I/PGII ≤4.0 [13]; (4) exclude patients with PG I ≥100 ng/mL from group A [14]; and (5) any of the above.…”
Section: Methodsmentioning
confidence: 99%
“…KK-LC-1 may be a good candidate to help diagnose gastric cancer because of its high frequency of expression and specificity for tumors involving H. pylori infection. There is currently a risk of gastric cancer designated as the ABC(D) classification, which stratifies patients into three or four risk groups using H. pylori infection and atrophic gastritis by measuring anti-H. pylori IgG and pepsinogen I/II in serum (16). However, it is difficult to detect patients with gastric cancer even in the high-risk group (high H. pylori titer and low pepsinogen, and high or low H. pylori titer and high pepsinogen) because fewer than 3% of the tumors are detected (17).…”
Section: Figure 1 Relationship Between Anti-helicobacter Pylori Igg mentioning
confidence: 99%